Gef10 - the third member of a Rho-specific guanine nucleotide exchange factor subfamily with unusual protein architecture - Mohl, Marion; Winkler, Stefan; Wieland, Thomas; Lutz, Susanne (Naunyn-Schmiedeberg's archives of pharmacology, 2006)
According to cDNA sequence homologies, Gef10 is related to the Rho-specific guanine nucleotide exchange factors GrinchGEF and p164-RhoGEF. Like these GEFs, Gef10 exhibits only weak homology to known pleckstrin homology domains, but contains a putative WD40-like domain. As detected by RT-PCR, Gef10 is transcribed in at least two splice variants in different human tissues. Although the Gef10 sequence contains two putative transmembrane segments, recombinantly expressed Gef10 displays a cytosolic localisation. As detected by guanine nucleotide exchange activity assay, precipitation assay of GTP-bound Rho proteins and serum response element dependent gene transcription Gef10 activates RhoA-C, but not Rac1 or Cdc42. In the reporter gene assay, Gef10 preferentially activated RhoB. When expressed in NIH3T3 cells, Gef10 induced actin stress fibre, but not lamellipodia or filopodia formation. We conclude that Gef10 is the third member of a Rho-specific GEF family with unusual protein architecture.